2012
DOI: 10.1007/s11948-012-9364-9
|View full text |Cite
|
Sign up to set email alerts
|

Collegial Ethics: Supporting Our Colleagues

Abstract: The goal of collegial ethics is to actively support our colleagues and to develop the skills needed to do so. While collegial interactions are key for our careers, there is little or no training in this. Many of our actions and reactions with our colleagues are instinctive. Human nature has evolved to be self-protective, but many evolved and automatic responses to others are not always in the best interests of our society or of us. Developing courage and a style of supportive language, avoiding destructive act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Bird has reported that even mentors may demonstrate “a misuse of power” (Bird, 2001 ). In contrast, Kuhar and Cross have pointed out that “The goal of collegial ethics is to actively support our colleagues … the golden rule” (Kuhar and Cross, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bird has reported that even mentors may demonstrate “a misuse of power” (Bird, 2001 ). In contrast, Kuhar and Cross have pointed out that “The goal of collegial ethics is to actively support our colleagues … the golden rule” (Kuhar and Cross, 2013 ).…”
Section: Discussionmentioning
confidence: 99%